Severe hypertension in elapid envenomation - Meenakshisundaram, Ramachandran (2013)
Snakebite is not an uncommon medical emergency in India; however, symptoms of autonomic dysfunction in snakebite are rare. The elapid snake envenomation is a frequent occurrence in India, and the krait bite is prevalent in the south Indian region. Here, we present three cases of snakebite with severe hypertension and requiring intravenous nitroglycerin (NTG). As the level of blood pressure (BP) decreased significantly following antisnake venom (ASV) injection in all three cases, it is likely that snake venom-induced dysautonomia might have contributed to severe hypertension in such patients. Clinical and therapeutic challenges of these cases are highlighted, so that practitioners coping with medical emergencies in resource-limited situations can consider snake (krait) bite in the differential diagnosis, and also manage effectively according to corroborative clinical evidences.